2023
DOI: 10.1186/s40001-023-01507-7
|View full text |Cite
|
Sign up to set email alerts
|

Adhatoda vasica and Tinospora cordifolia extracts ameliorate clinical and molecular markers in mild COVID-19 patients: a randomized open-label three-armed study

Mukta Verma,
Neha Rawat,
Ritu Rani
et al.

Abstract: Background SARS-CoV-2 infections caused mild-to-moderate illness. However, a sizable portion of infected people experience a rapid progression of hyper-inflammatory and hypoxic respiratory illness that necessitates an effective and safer remedy to combat COVID-19. Methods A total of 150 COVID-19-positive patients with no to mild symptoms, between the age groups 19–65 years were enrolled in this randomized, open-labeled three-armed clinical trial. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…All three treatment arms prevented the disease's progression to its more severe stages . Immunomodulatory activity of Guduchi, antiinflammatory, anti-hypoxic, and anti-thrombotic effects were observed for Adhatoda at preclinical levels and clinical study [149,170]. This is also the first report of in-depth analysis of clinical outcomes of Ayurvedic interventions on COVID-19 mild cases, assessed through multiple parameters analyzed at different time points .…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…All three treatment arms prevented the disease's progression to its more severe stages . Immunomodulatory activity of Guduchi, antiinflammatory, anti-hypoxic, and anti-thrombotic effects were observed for Adhatoda at preclinical levels and clinical study [149,170]. This is also the first report of in-depth analysis of clinical outcomes of Ayurvedic interventions on COVID-19 mild cases, assessed through multiple parameters analyzed at different time points .…”
Section: Introductionmentioning
confidence: 64%
“…During the outbreak of Covid-19, different extracts of Tinospora cordifolia was used as a herbal medicine for controlling fever, cough, immunity modulator and throat infections . The first clinical evidence of HIF-1 reduction in COVID-19 patients receiving AV herbal extract treatment was documented [149,170]. This study concluded that the use of oral medication of Vasa ghan, Guduchi ghan, and Vasa Guduchi ghan are effective treatment for mild COVID-19 patients [149,170].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In another study, Adhatodine and vasnetine showed a binding affinity of −9.60 kJ/mol and −8.78 kJ/mol, respectively when docked with SARS-CoV-2 main protease (PDBID:6Y84), viral protein targets [ 132 ]. Recently the first clinical evidence of HIF-1 reduction in COVID-19 patients receiving AV herbal extract treatment established the potential of AV to be safe and efficacious interventions for COVID-19 [ 133 ]. The in-vitro and in-silico analysis strongly suggest that it may have the ability to inhibit the SARS-CoV2 infection and its progression sequelae, thus AV being relevant treatment to the global pandemic of the microscopic demon COVID-19.…”
Section: Pharmacologymentioning
confidence: 99%